Language Assessment in Multilingualism and Awake Neurosurgery - De Martino, Maria; Talacchi, Andrea; Capasso, Rita; Mazzotta, Annapina; Miceli, Gabriele (Frontiers in Human Neuroscience, 2021)
Multilingualism has become a worldwide phenomenon that poses critical issues about the linguistic assessment in patients undergoing awake neurosurgery in eloquent brain areas. The accuracy and sensitivity of multilingual perioperative linguistic assessment procedures is crucial for a number of reasons: they should be appropriate to detect deficits in each of the languages spoken by the patient; they should be suitable to identify language-specific cortical regions; they should ensure that each of the languages of a multilingual patient is tested at an adequate and comparable level of difficulty. In clinical practice, a patient-tailored approach is generally preferred. This is a necessary compromise since it is impossible to predict all the possible language combinations spoken by individuals and thus the availability of standardised testing batteries is a potentially unattainable goal. On the other hand, this leads to high inconsistency in how different neurosurgical teams manage the linguistic features that determine similarity or distance between the languages spoken by the patient and that may constrain the neuroanatomical substrate of each language. The paper reviews the perioperative linguistic assessment methodologies adopted in awake surgery studies on multilingual patients with brain tumour published from 1991 to 2021 and addresses the following issues: 1. the language selected for the general neuropsychological assessment of the patient; 2. the procedures adopted to assess the dimensions that may constrain language organization in multilingual speakers: age and type of acquisition, exposure, proficiency and use of the different languages; 3. the type of preoperative linguistic assessment used for all the languages spoken by the patient; 4. the linguistic tasks selected in the intraoperative setting. The reviewed data show a great heterogeneity in the perioperative clinical workup with multilingual patients. The only exception is the task used during language mapping, as the picture naming task is highly preferred. The review highlights that an objective and accurate description of both the linguistic profile of multilingual patients and the specific properties of the languages under scrutiny can profitably support clinical management and decision making in multilingual awake neurosurgery settings.